FIGURE 29 in A small collection of rare and new chitons (Mollusca: Polyplacophora) from the Tasmanian Museum and Art Gallery - Sirenko, Boris (Zenodo, 2023)
FIGURE 29. Stenosemus simplicissimus, Southern Ocean, Heard Island, (TMAG, E 26179), BL 20.0 mm: A. Ventral scales and marginal spicules; B. Middle part of radula; C. Dorsal corpuscles; D. Central, first lateral teeth of radula and head of major lateral teeth of radula. Published as part of Sirenko, Boris, 2023, A small collection of rare and new chitons (Mollusca: Polyplacophora) from the Tasmanian Museum and Art Gallery, pp. 359-392 in Zootaxa 5325 (3) on page 384, DOI:10.11646/zootaxa.5325.3.3, http://zenodo.org/record/8247001